Islamic Parenting Psychoeducation: Marriage Dispensation Prevention in Ketawanggede Lowokwaru Malang - Zakiyah, Ermita; Nikmah, Faridatun; Magfiroh, Norma Hasanatul; Mukharomah, Awwalina (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
The current society has a significant prevalence of marriage dispensations. This situation is cause for concern, as marriage dispensation is consistently associated with early marriage, which might yield adverse consequences for those involved. There is a pressing requirement for the implementation of a comprehensive educational program within the community, aimed at mitigating the prevalence of marriage dispensations in society. One potential approach to address this issue is using Islamic parenting psychoeducation. This service used the Participation Action Research (PAR) technique, which entails the engagement of multiple stakeholders in evaluating all conducted activities and actions. The findings indicated a notable rise in the comprehension of female PKK cadres in Ketawanggede Village, Lowokwaru District, Malang City, regarding the marriage dispensations and its prevention. The findings indicate that the provision of psychoeducation has a beneficial impact on enhancing the comprehension of female PKK cadres in Ketawanggede Village, Lowokwaru District, Malang City.